Medical Students’ Perception of Learning Environment in New Campus of University Malaysia Sarawak (UNIMAS): Measured by DREEM - Khin, Than Yee; Myat, San Yi; Khin, Cho Aung; Mar, Mar Lwin; Mi, Mi Khaing; Tin, Moe Nwe; San, San Oo; San, Thitsa Aung; Thant, Zin; Mahadeva Rao, U. S. (RJPT, 2019)
Background: The ultimate goal of the medical education is to produce the competent and qualified medical professionals. One essential component of medical education is to provide a good learning environment. The assessment of learning environment has been determined as a key instrument for the delivery of high quality and effective education and curriculum. Objective of this study: It is to evaluate the strengths and weaknesses of learning environment in new campus of medical faculty in Kotasamarahan. Methods: It was a cross-sectional, questionnaire based study and ninety year-two medical students were recruited for the study. Dundee Ready Education Environment Measure (DREEM) questionnaire was used to collect the data. Results: The total score of DREEM was 124.05 / 200 and scores of all subdomains indicate ‘More positive than negative’ however there are items, 3,4,9,14,17,25,27 and 48 scored <2 which need improvements to be made to further enhance the quality of learning environment in new medical faculty of UNIMAS. Conclusion: This study can be used as a pivoting point to help produce more competent medical graduates in the future with the implementation of an efficient learning environment